Ocena rozwoju mowy dzieci dwujęzycznych – znaczenie wczesnej diagnozy dla rozpoznania i terapii zaburzeń - Korendo, Marta; Błasiak-Tytuła, Marzena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The authors emphasize the importance of language diagnosis of children raised in bi- or multiculturalism in early identification of developmental disorders. In the diagnostic process, they distinguish between skills independent of culture and those culturally (environmentally) conditioned, like the language system. They discuss the causes of speech development delays from a neurobiological and social (environmental) perspective. The article also includes short case reports.